Comparative Analysis of Shooting Consistency Among Archers of Different Skill Levels - Zhang, Baifa; Lin, Zhi-Cheng (Quality in Sport, 2024)
Purpose: This study aimed to investigate the biomechanical and electromyographic factors underlying shooting consistency among archers of different skill levels, providing insights into performance optimization and training strategies. Methods: The study analyzed 28 left-handed archers, including elite, mid-level, and novice athletes. Using an eight-camera infrared motion capture system and a wireless surface EMG system, kinematic and muscle activity data were collected for key upper limb muscles during two action phases: drawing and aiming. Coefficients of variation (CV) were calculated for both kinematic and EMG parameters, and statistical analysis was conducted to compare the groups. Results: Elite and mid-level archers exhibited significantly lower CVs in key kinematic parameters (e.g., shoulder abduction) and muscle activation consistency during the drawing phase compared to novices. Differences in muscle activation were most pronounced in the flexor muscle groups. These findings highlight the critical role of movement consistency in archery performance. Conclusion: Greater consistency in kinematic and muscle activation patterns distinguishes higher-skilled archers, particularly during the drawing phase. These results emphasize the importance of targeting movement consistency and coordination in training programs to enhance performance in precision sports like archery.